Збереження та розвиток козацьких традицій Волинського краю у доробку Григорія Гуртового - Олешко, П. (Краєзнавство, 2019)
Аналізується внесок Григорія Олександровича Гуртового (1924–2012) в суспільно-політичне, історико-краєзнавче та наукове життя Волині у другій половині ХХ – на початку ХХІ століть у контексті збереження та розвитку козацьких традицій Волинського краю. Hryhorii Hurtovyi’s contribution to the social and political, historical and scientific life of Volhynia in the second half of the XX and the beginning of the XXI centuries in the context of the preservation and development of Cossack traditions of Volyn region is analyzed in the article. The relevance of the study is determined by the value of Hryhorii Hurtovyi’s achievements, as a well-known teacher, researcher, historian, founder and director of the Torchyn Folk Museumof Local History. The spectrum of the scientific problems raised and studied by HryhoriiHurtovyi is extremely wide and varied. This is a series of works on Cossack topics, culminating in two editions of the monograph «Volyn Is the Land of Cossacks» (2000, 2009); the history of cities and villages of Lutsk district; the revival of truth and elimination of «white spots» in the history of Volhynia and Ukraine, etc. Numerous students and followers of HryhoriiHurtovyi, the Honorary Professor of LesiaUkrainka Eastern European National University, continue to enrich the theory and practice of Volyn regional studies. Scientific and practical conferences «Volyn Is the Land of Cossacks», initiated by HryhoriiHurtovyi, are held. The First Volyn Regional Local Lore Readings, dedicated to the memory of HryhoriiHurtovyi, were significant contribution to the study of the phenomenon of outstanding personality of the museum founder, as well as the extension of the problems of museum and local lore studios and introduction of a number of new documents into the scientific circulation. The problem of Hryhorii Hurtovyi’s role and contribution to the history of creation of the state and museum pedagogy, require scientific thinking and consideration, as well as special researches.